2019
DOI: 10.3389/fmicb.2019.01810
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Antifungal Activity of Hypocrellin A Against Candida albicans

Abstract: Many studies have reported that hypocrellin A (HA) exhibits effective antimicrobial activities with proper irradiation. However, its antifungal activity and the involved mechanism have not been fully defined. In this study, HA-mediated cytotoxicity in Candida albicans cells was evaluated after antimicrobial photodynamic therapy (aPDT). The results showed that 1.0 μg/ml HA significantly decreased the survival rate of C. albicans cells with light illumination. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Some studies have shown the fungicidal effect of photodynamic therapy against T. rubrum and T. mentagrophytes using CO 2 (De Oliveira et al, 2015) and toluidine (Baltazar et al, 2013), as well as with hypericin, hypocrillin, and curcumin as photosensitizers against Candida spp. ( Davies et al, 2016;Yang et al, 2019). Cyclic chalcones have significant characteristics for effects in PDT (Melo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the fungicidal effect of photodynamic therapy against T. rubrum and T. mentagrophytes using CO 2 (De Oliveira et al, 2015) and toluidine (Baltazar et al, 2013), as well as with hypericin, hypocrillin, and curcumin as photosensitizers against Candida spp. ( Davies et al, 2016;Yang et al, 2019). Cyclic chalcones have significant characteristics for effects in PDT (Melo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the wound infection area, a decrease in the CFU of yeast was noted. Authors explained such phenomenon by immune response reported before activation [251]. Jan et al evaluated 60 as a PS against yeast.…”
Section: Other Photosensitizersmentioning
confidence: 99%
“…These compounds are perylenequinone dyes derived from Hypocrella bambusae [250]. Yang et al studied 59 as a candidate for a PS for C. albicans combat [251]. Furthermore, 59 is known as an efficient producer of ROS including singlet oxygen, hydroxyl and superoxide radicals [5].…”
Section: Other Photosensitizersmentioning
confidence: 99%
“…Yang et al [56] investigated aPDT with hypocrellin A (HA). This PS compound displayed effective antimicrobial activity when irradiation was adequate irradiation.…”
Section: Natural Dyesmentioning
confidence: 99%